Assessment of Displacement Flow at Ketandan Creeks to Optimizing Land Use in Jember New City Housing - Entin Hidayah; Wiwik Yunarni Widiarti; Anik Ratnaningsih (IPTEK The Journal for Technology and Science, 2015)
Displacement flow will caused a change in the flow characteristics such as flow depth, discharge, river slope and width of the river surface. If not carefully examined, it will cause the riverbed erosion, sedimentation and risk of flooding. This paper aims to assess the hydrology and hydraulics of the river flow changes in Ketandan creek in optimizing the use of land housing for Jember New City (JNC). Hydrology modelling studies conducted for the return period rainfall include a 2 year as normal discharge, and 100 year as flood condition. Simulation of flood designs used to assess changes in the flow regime in the channel and the risk of flooding with HEC-RAS program. The results of the study showed that for the flood design 3,1 m3/sec and 12,8 m3/sec will give the effect of critical water surface. In order to keep the flow of the river bed of critically needed as the drop-structure and spillway construction